El museo como representación de los conflictos culturales - Cerón, Jaime (CALLE14: revista de investigación en el campo del arte, 2011)
This article tries to elucidate the manner in which the expository context activates in the spectator the capacity of projecting her own elaborations as the meaning of the works of art. Following Douglas Crimp, it explores the logical principles that are read as the mark of coherence of the museum space and that are in conflict with the social uses that are projected on it. Through the analysis of projects carried out by Daniel Buren, Hans Haacke, Marcel Broodthaers and Fred Wilson, it inquires in the manner in which cultural conflicts intertwined in the museum constitute the backdrop of an important segment of artistic practices of the last forty years. Finally, it examines the conceptual foundations of the museums of modern art, to check on their capacity to face contemporary art.